Meningioma growth dynamics assessed by radiocarbon retrospective birth dating - Huttner, Hagen B.; Bergmann, Olaf; Salehpour, Mehran; El Cheikh, Raouf; Nakamura, Makoto; Tortora, Angelo; Heinke, Paula; Coras, Roland; Englund, Elisabet; Eyüpoglu, Ilker Yasin; Kuramatsu, Joji; Röder, Sebastian; et al. (EBioMedicine, 2018)
It is not known how long it takes from the initial neoplastic transformation of a cell to the detection of a tumor, which would be valuable for understanding tumor growth dynamics. Meningiomas show a broad histological, genetic and clinical spectrum, are usually benign and considered slowly growing. There is an intense debate regarding their age and growth pattern and when meningiomas should be resected. We have assessed the age and growth dynamics of 14 patients with meningiomas (WHO grade I: n=6 with meningothelial and n=6 with fibrous subtype, as well as n=2 atypical WHO grade II meningiomas) by combining retrospective birth-dating of cells by analyzing incorporation of nuclear-bomb-test-derived 14C, analysis of cell proliferation, cell density, MRI imaging and mathematical modeling. We provide an integrated model of the growth dynamics of benign meningiomas. The mean age of WHO grade I meningiomas was 22.1±6.5years, whereas atypical WHO grade II meningiomas originated 1.5±0.1years prior to surgery (p<0.01). We conclude that WHO grade I meningiomas are very slowly growing brain tumors, which are resected in average two decades after time of origination.
EVALuna2:34031